Development and evolution of detachment faulting along 50 km of the Mid‐Atlantic Ridge near 16.5°N. (5th December 2014) - Smith, Deborah K.; Schouten, Hans; Dick, Henry J. B.; Cann, Johnson R.; Salters, Vincent; Marschall, Horst R.; Ji, Fuwu; Yoerger, Dana; Sanfilippo, Alessio; Parnell‐Turner, Ross; Palmiotto, Camilla; Zheleznov, Alexei; et al.
Abstract A multifaceted study of the slow spreading Mid‐Atlantic Ridge (MAR) at 16.5°N provides new insights into detachment faulting and its evolution through time. The survey included regional multibeam bathymetry mapping, high‐resolution mapping using AUV Sentry, seafloor imaging using the TowCam system, and an extensive rock‐dredging program. At different times, detachment faulting was active along ∼50 km of the western flank of the study area, and may have dominated spreading on that flank for the last 5 Ma. Detachment morphologies vary and include a classic corrugated massif, noncorrugated massifs, and back‐tilted ridges marking detachment breakaways. High‐resolution Sentry data reveal a new detachment morphology; a low‐angle, irregular surface in the regional bathymetry is shown to be a finely corrugated detachment surface (corrugation wavelength of only tens of meters and relief of just a few meters). Multiscale corrugations are observed 2–3 km from the detachment breakaway suggesting that they formed in the brittle layer, perhaps by anastomosing faults. The thin wedge of hanging wall lavas that covers a low‐angle (6°) detachment footwall near its termination are intensely faulted and fissured; this deformation may be enhanced by the low angle of the emerging footwall. Active detachment faulting currently is limited to the western side of the rift valley. Nonetheless, detachment fault morphologies also are present over a large portion of the eastern flank on crust >2 Ma, indicating that within the last 5 Ma parts of the ridge axis have experienced periods of two‐sided detachment faulting.